Pengembangan Layanan dan Pengenalan Akademik di Lingkungan Kampus berbasis Aplikasi Chatbot bagi Calon Mahasiswa Baru - Wicaksono, Damar; Salim, D Jayus Nor; Almeyda, Diva Putra (Jurnal Komtika (Komputasi dan Informatika), 2024)
Technology has a crucial role in information dissemination, creating a need for interactive and user-friendly communication tools. One of tools that can be used in this research is chatbot. Chatbots serve as effective intermediaries in the information exchange process, providing a simple and interactive interface. This research aims to develop a Button-Based Chatbot using the Smojo AI platform, with an easy-to-use interface for delivering college preparation information to prospective students. The development of the chatbot employs the SDLC Waterfall method. The chatbot is named "KaKa: Campus Companion" and it provides information on interest tests recommendations, effective study methods, admission pathways to public universities, and scholarship recommendations. The results of this research demonstrate the successful development of a chatbot that delivers simple and interactive information. The implementation of the SDLC Waterfall method in chatbot development ensures a well-structured and coordinated approach, focusing on each menu within the chatbot. Based on the test results, which have been carried out both white-box and black-box testing, the application can run correctly 100% and UAT testing with an accuracy level of 91%.